2020
DOI: 10.1142/s1793545820500236
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic detection of circulating melanoma cells in late stage patients

Abstract: Melanoma is the deadliest skin cancer and is responsible for over 7000 deaths in the US annually. The spread of cancer, or metastasis, is responsible for these deaths, as secondary tumors interrupt normal organ function. Circulating tumor cells, or those cells that spread throughout the body from the primary tumor, are thought to be responsible for metastasis. We developed an optical method, photoacoustic flow cytometry, in order to detect and enumerate circulating melanoma cells (CMCs) from blood samples of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Comparison of tissue from albino and pigmented rabbits showed that melanin was a particularly strong acoustic attenuator. Photoacoustic signals can also be used to reveal circulating melanoma cells by flow cytometry (O'Brien et al, 2012;Viator et al, 2020).…”
Section: Melanin and Ultrasoundsmentioning
confidence: 99%
“…Comparison of tissue from albino and pigmented rabbits showed that melanin was a particularly strong acoustic attenuator. Photoacoustic signals can also be used to reveal circulating melanoma cells by flow cytometry (O'Brien et al, 2012;Viator et al, 2020).…”
Section: Melanin and Ultrasoundsmentioning
confidence: 99%
“…Our primary source was Google Scholar, which yielded 12,300 total results. Of the 12,300 results, 102 studies 103,109,113,[115][116][117][132][133][134][135][136][137][138][139][140] met our criteria and are reviewed here. 3 Investigations of CM Using PAI…”
Section: Methodsmentioning
confidence: 99%
“…Our primary source was Google Scholar, which yielded 12,300 total results. Of the 12,300 results, 102 studies 103 , 109 , 113 , 115 117 , 132 140 , 165 245 met our criteria and are reviewed here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Особенно заметным это оказалось в рамках серии клинических испытаний, посвященных задаче неинвазивного дифференциального диагноза доброкачественных и злокачественных новообразований, выявленных при скрининге у лиц в группе риска (хронические курильщики, страдающие хронической обструктивной болезнью легких) [104]. Существует ряд более современных методик, использующих магнитоэлектрические, деформационные, оптические или акустические воздействия для селекции опухолевых клеток [105][106][107].…”
Section: циркулирующие опухолевые клетки (цок)unclassified